Influence of secretory leukocyte protease inhibitor (SLPI) basedeptides on elastase activity and their incorporation into hyaluronic acid hydrogels for chronic wound terapy - Barros, Sandra Cerqueira (2012)
Chronic nonhealing skin wounds, such as leg ulcers and pressure sores, represent a major clinical problem and a financial burden for the health care systems. Chronic wounds are characterized by prolonged inflammatory phase that results in high levels of elastase, reactive oxygen species (ROS), and diminished growth factor activity. Under normal physiological conditions, elastase is a powerful host defence and its activity is regulated by endogenous inhibitors. The unrestrained elastase activity in chronic wounds may be tuned by exogenous active materials that inhibit elastase. Secretory leucocyte protease inhibitor, SLPI, is a potent endogenous inhibitor of elastase. Peptide fragments, KRCCPDTCGIKCL (Pep4) and KRMMPDTMGIKML (Pep4M), selected from SLPI primary structure were studied as potential elastase inhibitors. Kinetic studies performed for human neutrophil elastase (HNE) and porcine pancreatic elastase (PPE) in presence of these peptides revealed that both behave as uncompetitive and noncompetitive inhibitors of HNE and PPE, respectively. The influence of ROS and albumin on Pep4 and Pep4M inhibitory activity toward elastase reveals that this mixture increases the inhibitory activity of both peptides. These peptides were incorporated in hyaluronic acid hydrogels to evaluate the possibility of being used as active compounds in a drug delivery system. Assessment of HNE and PPE activity in the presence of these hydrogels formulations revealed a considerable decrease in enzyme activity. Although, only moderated elastase inhibition was observed, these peptides represent potential candidates for chronic wound applications, as there is no need for complete elastase inhibition in the normal wound healing process